The Rise of School Choice in Education Funding Reform: An Analysis of Two Policy Moments. (March 2014) - Windle, Joel
This article contributes to the analysis of the global spread of support for school choice and to the understanding of how a particular form of policy development reflects and cements this support. It maps the growing dominance of school choice within a reconfiguration of politics, policy making, and research. To establish the nature of this reconfiguration, a comparison is made between the Karmel Review, which established systematic federal government intervention in Australian schooling, and the Gonski Review. The analysis traces a move away from a social-democratic model built around an autonomous and representative government authority in which educational research was broadly writ, to a neoliberal model under direct government control, drawing selectively on a cast of corporate consultants and technocrats. I conclude with a consideration of the wider implications of the dominance of school choice as a paradigm for funding reform.